Use of alveolar distraction osteogenesis for anterior maxillary defect reconstruction - Marcantonio, Cláudio (2019)
Alveolar osteogenic distraction (AOD) is a biological process through which new bone formation occurs between bone segments that are gradually separated by incremental traction. This case report described the oral rehabilitation with dental implants of a patient with a vertical bone defect in the maxillary anterior region using the AOD technique. The patient presented with absence of the teeth 22, 21, 11, and 12 associated with a vertical bone defect. The AOD was performed using a supported osteodistractor device surgically installed with subsequent daily activations. After 21 days, the ideal positioning of bone fragment was confirmed and activation was ceased. Five months after the initial surgery, two dental implants were installed in the region of teeth 12 and 22. An FP3 metal-ceramic prosthesis was installed offering satisfactory esthetic results. In conclusion, the use of AOD to increase the alveolar ridge was effective and ensured rehabilitation with dental implants.